From Aristotelianism to Galilean science: Paolo Sarpi's natural philosophy. Issue 2 (3rd April 2022) - Baldin, Gregorio
ABSTRACT: Histories of philosophy do not even dedicate a paragraph to Paolo Sarpi. He is usually considered solely as a historian and polemicist, at most as a fine political thinker, but historians of early modern philosophy have never paid attention to his natural philosophy. This article aims to consider Sarpi's thought in relation to modern philosophy and science, by examining his relationship with Galileo's philosophy, his gnoseology and epistemology, and his natural philosophy, which emerge from his collection of Pensieri (thoughts). Sarpi's attempt to overcome the horizon of Scholastic Aristotelianism and to lay the foundations of a new natural philosophy appears in this analysis. He anticipated and contributed, in this way, to the genesis of Galileo's philosophy and, therefore, to the birth of modern philosophy and science.